2014
DOI: 10.1007/s10453-014-9337-3
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric concentrations of Alternaria, Cladosporium, Ganoderma and Didymella spores monitored in Cork (Ireland) and Worcester (England) during the summer of 2010

Abstract: This study represents the first international intercomparison of fungal spore observations since 1990, focusing on atmospheric concentrations of Alternaria, Cladosporium, Ganoderma and Didymella spores. The campaigns were performed at sites located in Cork (Ireland) and Worcester (England) during summer 2010. Observations were made using Hirsttype volumetric spore traps and corresponding optical identification at the genus level by microscope. The measurements at both sites (including meteorological parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 48 publications
6
33
1
Order By: Relevance
“…Similar to our findings, Cladosporium and Alternaria were found to have a positive correlation with temperature but a negative correlation with relative humidity (Recio et al, 2012;O'Connor et al, 2014). The spores of Cladosporium are considered dry air spores, thus the midday weather conditions when the temperature is relatively high and relative humidity decreases make it optimum for the dispersion of Cladosporium spores (Elvira , 2001).…”
Section: Diurnal Variation Of Fungal Spore Populations In the Atmosphsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to our findings, Cladosporium and Alternaria were found to have a positive correlation with temperature but a negative correlation with relative humidity (Recio et al, 2012;O'Connor et al, 2014). The spores of Cladosporium are considered dry air spores, thus the midday weather conditions when the temperature is relatively high and relative humidity decreases make it optimum for the dispersion of Cladosporium spores (Elvira , 2001).…”
Section: Diurnal Variation Of Fungal Spore Populations In the Atmosphsupporting
confidence: 83%
“…Recio et al (2012) concluded from their study that the highest correlation coefficients in term of maximum, mean and minimum temperature to be for Alternaria accordingly they recommended to predict the concentration of Alternaria spores as a function of temperature. It was demonstrated that the maximum release of Ganoderma spores occurred when the humidity increased and temperature diminished (O'Connor et al, 2014). Similarly, Calderon et al (1995) concluded that the release of basidiospores are negatively correlated with temperature and declines at higher temperature more than 27 0 C.…”
Section: Diurnal Variation Of Fungal Spore Populations In the Atmosphmentioning
confidence: 96%
“…Temperature, RH, rainfall, and dew point were all positively associated with the concentrations of fungal spores by up to lag day 1. Similar results have been reported in many studies in various geographical areas worldwide (Sousa et al, 2008;Ho et al, 2005;Quintero et al, 2010;Grinn-Gofroń et al, 2011;O'Connor et al, 2014). These relationships are most likely a result of the growth requirement of fungi through either a direct or indirect effect on water availability (a w ) (Burge and Otten, 1999).…”
Section: Discussionsupporting
confidence: 74%
“…information of only those spores with allergenic and/or phytopathogenic interest (O'Connor et al 2014;Pyrri and Kapnasaki-Gotsi 2015). The reason for that is the time commitment required and the difficulty of identifying fungal spores by non-viable methods as Hernández already observed.…”
Section: Introductionmentioning
confidence: 94%